O problema epistêmico dos QUALIA - Sant'anna, André Rosolem (2016)
One problem that occupies the agenda of many contemporary philosophers is whether we can justify our beliefs about the nature of other human beings and animals mental states. This problem arises because we cannot observe directly the mental states of other biological systems. Despite the fact that we have good practical reasons to believe that we share mental states of the same nature, the underlying theoretical motivations supporting this belief are not always so clear. In other words, although we do not take those questions into consideration when interacting with people on a daily basis, they do raise important concerns for philosophers. My aim in this dissertation is to establish the philosophical foundations for what I call an epistemic theory of qualia. In order to accomplish this goal, I bring important discussions going on in philosophy of mind and in philosophy of biology together as a means to justify our ordinary beliefs that other people and other animals have mental states with the same qualitative aspects. I start by discussing the problem with which I will be concerned, that is, the epistemic problem. I argue that a recent approach to the problem of mind-body interaction-functionalism-fails to deal with objections raised in relation to the qualitative aspects of mental states (qualia). I propose, as an alternative, a reformulation of functionalism by articulating the view in relation to some important notions in philosophy of biology, such as the notion of etiological functions. I then argue that this approximation allows us to formulate an epistemic theory of qualia which. solves the epistemic problem discussed previously.